Biochemistry - Garrett, R.
In Biochemistry, the questions often are more exhilarating than the answers. This Updated Third Edition continues the unique conceptual and organizing framework, "Essential Questions." Guiding students through the density of the material by the use of section head questions, supporting concept statements, and summaries, this focused approach is supported by unparalleled text/media integration through BiochemistryNow, providing students with a seamless learning system. Beautifully and consistently illustrated, this text gives science majors the most current presentation of biochemistry available. Written by a chemist and a biologist, the book presents biochemistry from balanced perspectives